Hubungan Komunikasi, Sumber Daya, Disposisi, dan Struktur Birokrasi dengan Implementasi Kawasan Tanpa Rokok (KTR) di Puskesmas Sanggeng Kabupaten Manokwari - Yaneke Yosister Henni Ramandei; Arius Togodly; Wahyuti Wahyuti; Sarce Makaba; Rosmin Tinggimenehe; Yacob Ruru (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
The implementation of the Smoke Free Area (SFA) policy is one of the public health strategies aimed at protecting communities from exposure to cigarette smoke. This study was conducted to analyze the relationship between communication, resources, disposition, and bureaucratic structure with the implementation of SFA policy at Sanggeng Health Center and to determine the most dominant factor influencing its implementation. This study employed an analytical observational design with a cross-sectional approach. The population consisted of all employees working at Sanggeng Health Center, Manokwari Regency. A total sampling technique was applied, involving 59 respondents. Data were analyzed using univariate analysis for frequency distribution, bivariate analysis using Chi-square/Fisher Exact Test, and multivariate analysis using logistic regression to identify the dominant variable. The results showed that most respondents perceived the implementation of SFA policy as good (76.3%). Bivariate analysis indicated that communication (p=0.198), resources (p=0.412), and disposition (p=0.666) were not significantly associated with Smoke Free Area implementation. In contrast, bureaucratic structure was significantly associated with SFA implementation (p=0.002; RP=1.688; 95% CI: 1.190–2.392). Multivariate analysis confirmed that bureaucratic structure was the most dominant factor, with respondents in a good bureaucratic structure having 16.88 times greater odds of achieving optimal SFA implementation compared with those in a poor bureaucratic structure (OR=16.880; 95% CI: 2.943–96.817; p=0.002). Conclusion: Bureaucratic structure was the only factor significantly associated with SFA implementation and emerged as the most dominant determinant. Strengthening organizational systems, including clear standard operating procedures, role distribution, and routine supervision, is essential to improve the effectiveness of Smoke Free Area implementation in primary healthcare facilities.